Answer:
![x = -7](https://tex.z-dn.net/?f=x%20%3D%20-7%20)
![y = - 12](https://tex.z-dn.net/?f=y%20%3D%20%20-%2012)
Step-by-step explanation:
The given system is:
4x-3y=8
5x-2y=-11
We make x the subject in the top equation to get:
![x = \frac{3}{4}y + 2](https://tex.z-dn.net/?f=x%20%3D%20%20%5Cfrac%7B3%7D%7B4%7Dy%20%2B%202)
Plug this expression for x in the bottom equation to get
![5( \frac{3}{4}y + 2) - 2y= - 11](https://tex.z-dn.net/?f=5%28%20%5Cfrac%7B3%7D%7B4%7Dy%20%2B%202%29%20-%202y%3D%20%20-%2011)
We expand to obtain
![\frac{15}{4} y + 10 - 2y = - 11](https://tex.z-dn.net/?f=%20%5Cfrac%7B15%7D%7B4%7D%20y%20%2B%2010%20-%202y%20%3D%20%20-%2011)
Multiply through by 4
![15y + 40 - 8y = - 44](https://tex.z-dn.net/?f=15y%20%2B%2040%20-%208y%20%3D%20%20-%2044)
Group similar terms
![15y - 8y = - 44 - 40](https://tex.z-dn.net/?f=15y%20-%208y%20%3D%20%20-%2044%20-%2040)
![7y = - 84](https://tex.z-dn.net/?f=7y%20%3D%20%20-%2084)
![y = - \frac{84}{7} =-12](https://tex.z-dn.net/?f=y%20%3D%20%20-%20%20%5Cfrac%7B84%7D%7B7%7D%20%20%3D-12%20)
This means
![x = -12\times \frac{3}{4} + 2](https://tex.z-dn.net/?f=x%20%3D%20%20-12%5Ctimes%20%20%5Cfrac%7B3%7D%7B4%7D%20%20%2B%202)
![x = - 7](https://tex.z-dn.net/?f=x%20%3D%20%20-%207)
JK = MN because of Given
∠JLK = ∠MLN because of the vertical angle theorem
JL = LN because of definition of midpoint
ΔJLK = MLN because of SAS
∠K = ∠N because corresponding angles of congruent triangles are congruent.
Hope this helps!<span />
Answer is B
-0.6- (-0.4)= -0.6+0.4= -0.2
Answer: £54.60
Step-by-step explanation:
7.80 x 7 = £54.60
***If you found my answer helpful, please give me the brainliest. :) ***